Analysis Of The Compilation Review Of Islamic Law On Interfaith Marriages From A Sharia Perspective - Muhammadong Muhammadong (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
The purpose of this research is to find out a review of the compilation of Islamic law regarding interfaith marriages from a sharia perspective. The method used in this research is qualitative, with a comparative approach by conducting literature studies related to studies of theories relevant to the problem of interfaith marriages. In the view of Islamic law, marriage between different religions is strictly prohibited because it is contrary to the rules of Islamic law in maintaining the existence of religion. The goal of marriage is to create a sakinanh, mawaddah wa Rahmah household, but this goal is very difficult to realize if the marriage is built on the basis of different religions. Based on Marriage Law Number 1 of 1974 which is implemented in the compilation of Islamic law, it states that it does not accommodate interfaith marriages to strengthen the arguments put forward in the Koran.